A thematic review on souvenirs from design perspective publications from 2012–2022: analysis of trends for future studies - Zhu, Qiuxia; Abdul Rahman, Ahmad Rizal; Huang, Wenhong (Taylor and Francis Group, 2022)
As cultural tourism expands, globalisation and localisation have become contradictory terms. Souvenirs are fast becoming crucial for promoting cultural tourism while maintaining a pivotal role in enhancing a country’s image. Design is essential for souvenir production and the primary method by which souvenirs create value. Despite the growing number of publications on souvenirs, few reviews examine the development and strategies of souvenir design and its future directions. Therefore, this study’s specific aim is to report on the outcomes of a thematic review analysis examining souvenir research from a design perspective, addressing the knowledge and methods required in practice-based souvenir design. Data for this study were collected using a thematic review analysis of 51 publications from 2012 to 2022, and the ATLAS.ti 8 code-to-document review findings indicate the patterns needed by researchers. The analysis shows five central themes: 1) culture-oriented design; 2) customer-oriented product design; 3) design method; 4) regional development; and 5) sustainability. The results suggest that future research trends in souvenir design should focus on locality-based development strategies and sustainability for promoting local culture and economies. This work will generate fresh insight into new guidelines for research trends in souvenir design.